Enabling ocean research in the 21st century : implementation of a network of ocean observatories (National Academies Press, 2003)
The report evaluates the scientific and technical readiness to move ahead with the establishment of a research-driven ocean observatory network, and to highlight the outstanding issues. These issues include the status of planning and development, factors that affect the timing of construction and installation, the cost and requirements for maintenance and operations, needs for sensor development and data management, the impact on availability of ships and deep submergence facilities, and the role of research-based observatories within national and international operational ocean observing systems being developed and implemented.